Assessment Of Public Perceptions Of Community Pharmacies As Primary Healthcare Hubs Under Vision 2030 Reforms (The Review of Diabetic Studies, 2024)
Background: Community pharmacies are increasingly recognized as accessible and trusted healthcare providers. Under Saudi Arabia’s Vision 2030 reforms, their role is expanding beyond traditional medication dispensing to include preventive care and chronic disease management. This study assessed public perceptions of community pharmacies as primary healthcare hubs and identified factors influencing engagement.Methods: A cross-sectional survey was conducted among 236 participants across Saudi Arabia. Data were collected on perceptions of pharmacy services, trust in pharmacists, utilization of preventive care, and demographic factors. Descriptive and inferential analyses were performed to examine relationships between educational attainment, frequency of pharmacy visits, and public perceptions.Results: The majority of participants demonstrated strong support for the evolving role of community pharmacies, with 93% strongly agreeing that pharmacies can provide healthcare services beyond dispensing. High levels of trust were reported in pharmacists’ expertise for medication counseling (96%) and chronic disease management (88%). However, utilization of preventive services, such as vaccinations (23%) and health screenings (19%), remained limited. Positive perceptions were significantly associated with higher education levels and frequent pharmacy engagement. Participants highlighted accessibility, private consultation areas, effective communication, and extended hours as key determinants of engagement.Conclusion: The findings indicate that the Saudi public strongly endorses community pharmacies as primary healthcare hubs. While trust and awareness are high, gaps remain in the uptake of preventive services. Policy and practice strategies—including public education, operational enhancements, and professional development—are recommended to optimize pharmacy-based healthcare delivery and align with Vision 2030 objectives.